Effect of dietary DHA/EPA ratio on the early development, antioxidant response and lipid metabolism in larvae of Siberia sturgeon (Acipenser baerii, Brandt). (23rd October 2018) - Luo, Lin; Ai, Lichuan; Liang, Xiaofang; Xing, Wei; Yu, Huanhuan; Zheng, Yinhua; Wu, Xiufeng; Liang, Xufang; Xue, Min
Abstract: A 30‐day growth study was conducted to evaluate the impacts of the dietary DHA/EPA ratios on growth performance, antioxidant and lipid metabolism of Siberian sturgeon larvae. Four isonitrogenous and isoenergetic microcapsuled diets were formulated with various DHA/EPA ratios as 0.73 (R0.73 ), 1.25 (R1.25 ), 1.75 (R1.75 ) and 2.33 (R2.33 ). The results showed that the final body length, final body weight, specific growth rate and survival in the group R2.33 were highest ( p < 0.05), while there were no significant differences on viscerosomatic index and condition factor among all groups. Visceral catalase activity of groups R2.33 and R1.75 was significantly higher than that of groups R0.73 and R1.25, but superoxide dismutase, total antioxidant capacity, malondialdehyde, total cholesterol, triglycerides and high‐density cholesterol were not different among groups. The gene expression of PPARα and lipoprotein lipase had no difference among groups, but the expression of hepatic lipase gene in groups R1.75 and R2.33 was significantly lower than that in group R0.73 as a negative feedback of high dietary DHA intake. In conclusion, growth performance was improved but kept stable antioxidant response in visceral mass with increased levels of DHA/EPA ratios from 0.73 to 2.33 for Siberian sturgeon larvae. Improving DHA/EPA ratios is a benefit for larvae to selectively deposit more DHA, then EPA and ARA than MUFA in the body to meet the requirement for early development.